Effectiveness of Administrative Service Forms in Implementing School Administrative Staff Duties at SMK TI Airlangga Samarinda - Maryani, Diana Tri; Pasaribu, Veta Lidya Delimah (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The background of this research is to find out how effective the form of administrative services at Airlangga IT Vocational School, Samarinda is. In addition, this research aims to identify factors that hinder and hinder administrative services, such as service processes, supporting factors, and types of Administrative Staff services at Airlangga IT Vocational School, Samarinda. The final aim of this research is to provide excellent administrative services at the Airlangga IT Vocational School, Samarinda. This research is descriptive qualitative research using observation and interview data collection methods. The Principal, Head of School Administrative Staff, Student Affairs, and Homeroom Teachers are the main data sources in this research. However, the methods used to carry out data analysis are data reduction, data presentation, and drawing conclusions. The results of this research show that the administrative service process at Airlangga Samarinda IT Vocational School is a series of activities or a whole process that monitors teamwork in a planned and systematic manner to achieve goals. This process is carried out in certain environments, especially in formal educational institutions which occur at the Airlangga IT Vocational School, Samarinda. The study results show that to achieve common goals, the administrative staff service process at Airlangga IT Vocational School Samarinda still requires good cooperation to maintain the best results. Apart from that, there are several obstacles that hinder the administrative staff service support process at Airlangga IT Vocational School Samarinda. Therefore, to achieve this, good motivation, encouragement and collaboration are needed.